Severe malarial anemia and cerebral malaria are associated with different tumor necrosis factor promoter alleles. - McGuire, W; Knight, J; Hill, A; Allsopp, C; Greenwood, B; Kwiatkowski, D (1999)
Experimental evidence implicates tumor necrosis factor (TNF) in the pathogenesis of malarial anemia, but there are few data relating to this hypothesis. This study found that severely anemic children with Plasmodium falciparum infection have low plasma TNF levels, in contrast to the high levels found in cerebral malaria. A previous case-control study in The Gambia found cerebral malaria, but not severe malarial anemia, was associated with the TNF-308 A allele. This study found that in the same population, severe malarial anemia was associated with the TNF-238 A allele, with an odds ratio of 2.5 (P<.001) after stratification for HLA type. These findings suggest that severe malarial anemia and cerebral malaria are influenced by separate genetic factors situated near the TNF gene.